Uterine leiomyomas in hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome can be identified through distinct clinical characteristics and typical morphology. (3rd September 2021) - Uimari, Outi; Ahtikoski, Anne; Kämpjärvi, Kati; Butzow, Ralf; Järvelä, Ilkka Y.; Ryynänen, Markku; Aaltonen, Lauri A.; Vahteristo, Pia; Kuismin, Outi
Abstract: Introduction: Hereditary leiomyomatosis and renal cell cancer (HLRCC) constitute a tumor susceptibility syndrome caused by germline mutations in the fumarate hydratase ( FH ) gene. The most common features are leiomyomas of the uterus and the skin. The syndrome includes a predisposition to early‐onset, aggressive renal cell cancer. It is important to identify women with HLRCC among other uterine leiomyoma patients in order to direct them to genetic counseling and to identify other affected family members. Material and methods: We conducted a nationwide historical study to identify typical clinical characteristics, uterine leiomyoma morphology, and immunohistochemistry for diagnosing HLRCC. The study included 20 women with a known FH germline mutation and 77 women with sporadic uterine leiomyomas. The patient records of all women were reviewed to obtain clinical details regarding their leiomyomas. Uterine leiomyoma tissue specimens from 43 HLRCC‐related leiomyomas and 42 sporadic leiomyomas were collected and prepared for histology analysis. A morphologic description was performed on hematoxylin & eosin‐stained tissue slides, and immunohistochemical analysis was carried out for CD34, Bcl‐2, and p53 stainings. Results: The women with HLRCC were diagnosed with uterine leiomyomas at a young age compared with the sporadic leiomyoma group (mean 33.8 years vs. 45.4 years, P < 0.0001), and their leiomyomas occurred as multiples compared with the sporadic leiomyoma group (more than four tumors 88.9% vs. 30.8%, P < 0.0001). Congruently, these women underwent surgical treatment at younger age compared with the sporadic leiomyoma group (mean 37.3 years vs. 48.3 years, P < 0.0001). HLRCC leiomyomas had denser microvasculature highlighted by CD34 immunostaining when compared with the sporadic leiomyoma group (112.6 mean count/high‐power field, SD 20.8 vs. 37.4 mean count/high‐power field, SD 21.0 P < 0.0001) and stronger anti‐apoptotic protein Bcl‐2 immunostaining when compared with the sporadic leiomyoma group (weak 4.7%, moderate 44.2%, strong 51.2% vs. 26.2%, 52.4%, 21.4%, respectively, P = 0.003). No differences were observed in p53 staining. Conclusions: Women with HLRCC may be identified through the distinct clinical characteristics: symptomatic and numerous leioymyomas at young age, and morphologic features of FH ‐mutant leiomyomas, aided by Bcl‐2 and CD34 immunohistochemistry. Further, distinguishing individuals with a germline FH mutation enables proper genetic counseling and regular renal monitoring.